Antioxidant effectivity to decrease coronal microleakage of composite resin restoration after intra-coronal bleaching - Yusri Yusri; Aries C. Trilaksana; Chiristine A. Rovani (DiscoverSys Inc., 2016)
This study aimed to compare the ability of the three antioxidant ingredients and a minimal application to decrease microleakage of composite resin restoration after intracoronal bleaching. Fifty maxillary first incisor that met the inclusion criteria were prepared endodontic treatment. They are divided into 10 groups: control group (no antioxidant), sodium ascorbate 10%, catalase 10% and sodium ascorbate 10% with Tween 80 0.2% and an application period of 1 hour, 24 hours and 48 hours. Applied hydrogen peroxide 35% for 5 days. Samples were restored with composite resin and coated with nail polish, placed China ink for 24 hours. Coronal microleakage was assessed using a stereomicroscope, which showed presented a significant different (Ï<0.05) in 48 hours. It was concluded that sodium ascorbate 10% with Tween 80 0.2% had a significant effect in decreasing coronal microleakage in 48 hours.